Estabelecimento de espécies florestais nativas, em área de restauração ciliar no Baixo Rio São Francisco - Aragão, Alexsandro Guimarães de (2009)
The process of environmental degradation that has been occurred in the lower region of Sao Francisco s river is reducing the permanent preservation areas. The artificial regeneration is a method of riparian restoration widely used to reconstitute the native vegetation in degraded areas. For the reasons set was a work of restoration in an area of riparian forest in Santana do São Francisco s county Sergipe, with the objective of proposing models to restore the natural balance of the environment. The studied area after tested was monitored for 60 months, using the experimental design in randomized blocks in three models restoration the riparian forest (seedlings growth of forest species in spacing 3x1,5m and 3x3m and direct seeding in spacing 3x1,5m) and twelve native forest species. There were evaluated seedling emergence, surviving and development of species tested (height, base diameter e the relative growth rate). Was also performed to evaluated phenological aspects of species tested and identified the presence of colonizing species in the studied area. The results after 60 months old of the implanted species indicated a higher percentage of surviving of species in the model with growth in spacing 3x1,5m (62,2%). It was observed that the spacement used not able to influence the development of species. To TCR (relative growth rate) was identified as the pioneer species Schinus terebinthifolius (Raddi.) had the highest rates of growth in height in three models implanted. With respect to the diameter base was observed that the species that showed the highest growth rates were Vitex polygama (Cham.), Schinus terebinthifolius (Raddi.) e Cassia grandis (L.f). Considering the phenological aspects were observed that five species (40%) showed flowering and fruiting during the 60 months of evaluation. The species studied showed up in the potential restoration of riparian forests and may be the recommended direct seeding method to reduce the costs of deployment in the lower region of Sao Francisco s river.